Masa Percobaan Pidana Mati Pada KUHP Nasional Ditinjau dari Aliran Utilitarianisme Hukum - Bertrand Jerison Gunawan; Go Lisanawati (Jurnal Hukum Lex Generalis, 2024)
This article aims to analyze the existing provisions in the Criminal Code of Indonesia regarding a trial period for the death penalty for convicts who do not regret their criminal conduct. It can be said that the convict has been sentenced twice. This method is a normative juridical because the focus of the study departs from the vagueness of norms, using approaches such as the statute approach and the conceptual approaches. This technique for searching legal materials uses document study techniques and normative analysis. Based on the results of the analysis, the trial period for the death penalty for convicts who do not regret their actions is ineffective. It is because it violates the human rights of the convict. After all they torture the convict by giving him probation for 10 years. Basically, the convict does not regret his actions so without having to wait a long time the death execution can be carried out. Keywords: Death Penalty; Human Rights, Trial Period;